Valutazione del turn over dei farmaci antiretrovirali in particolare da IP a NNRTI - Sabbatani, Sergio; Cesari, Raffaella; Pipitone, Emanuela; Chiodo, Francesco (Farmeconomia. Health Economics and Therapeutic Pathways, 2003)
Objective: To determine the turnover for each antiretroviral drugs present in TP’s of patients under care for HIV infection, with a special focus on PI’s and NNRTI’s. Design/Methods: We have carried out a retrospective analysis with the aim of evaluating the turnover of each drug in the 3-year period 1998-2000. Using a specifically designed software, it was possible to determine the changes in TP for each single patient. We then calculated a different weighted percentage for each drug on the basis of the time interval from the drug entry to its exclusion from the TP: the shorter the interval, the greater the assigned weight. Finally we carried out a cluster analysis in order to obtain homogeneous groups of molecules showing the same degree of therapy switches. We established that a higher average score corresponds to a higher therapy switch rate. Results: Zidovudine/Lamivudine combination, Indinavir, Lamivudine, Nerivapine and Nelfinavir are the drugs with the lowest turnover. On the other hand, Saquinavir, Didanosine, Zidavudine, and Stavudine show the highest turnover. Conclusion: The introduction of NNRTI’s with the associated switch from PI’s (Saquinavir, Nelfinavir) and the Zidavudine/Lamivudine combination enables a simplification of the treatment. This practice appeared to be a good choice in the 3-year period under consideration. The adoption of these therapeutic solutions reduce the turnover, consequently giving more stability to TP’s.